Perubahan Sosial Kehidupan Masyarakat Tahanan Politik Di Desa Savana Jaya Kecamatan Waeapo Kabupaten Buru - Ngilmy, Putri; Pusparani, Rina (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2024)
This study aims to explore the lives of political prisoners in Savana Jaya Village, Waeapo District, Buru Regency, and to reveal the social changes that have occurred in their lives. Through a descriptive qualitative approach, this research delves into the experiences and social dynamics of the political prisoners, most of whom were arrested, detained, and subjected to harsh treatment following the events of the September 30th Movement in 1965. Under military supervision, the political prisoners worked to clear forests and develop rice fields, transforming previously untouched wilderness into productive agricultural land. The interaction between the political prisoners and the indigenous population led to cultural and economic exchanges, introducing new farming techniques and improving local welfare. The research findings indicate significant economic, linguistic, and cultural changes, with intermarriage between groups leading to a blending of Javanese and Buru cultures. This study provides a comprehensive understanding of social changes on Buru Island and the contributions of the political prisoners in transforming the local socio-economic conditions.